2021
DOI: 10.1192/j.eurpsy.2021.839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 pandemic on mental health - what do we know so far?

Abstract: IntroductionThe devastating effects of the current pandemic are profoundly affecting peoples’s physical and psychological health. Numerous studies on the effects of previous infectious outbreaks have been published. Similarly, an increasingly growing body of research on COVID-19 has been developed and released, reporting a substancial psychological impact of both the outbreak and the response, suggesting that the population may express high levels of psychological symptoms.ObjectivesThis presentation aims to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Min et al ( 70 ) suggested that differential access to information may have contributed to the fact that people with higher SES were increasingly affected by the pandemic. Previous studies reported that people were exposed to anxiety-provoking information via social media, and more frequent exposure to such information may have led to higher vulnerability to mental-health deterioration when the future was unpredictable ( 91 ). In this regard, young, middle-aged, highly educated and high-income individuals were more likely to be exposed to negative information from the internet and social media than the general population ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Min et al ( 70 ) suggested that differential access to information may have contributed to the fact that people with higher SES were increasingly affected by the pandemic. Previous studies reported that people were exposed to anxiety-provoking information via social media, and more frequent exposure to such information may have led to higher vulnerability to mental-health deterioration when the future was unpredictable ( 91 ). In this regard, young, middle-aged, highly educated and high-income individuals were more likely to be exposed to negative information from the internet and social media than the general population ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies identified demographic subgroups at higher risk for mental-health problems during the COVID-19 pandemic. Concerning generational inequality, young adults were frequently mentioned as disproportionally vulnerable during the COVID-19 pandemic ( 29 , 30 , 50 , 54 , 55 , 62 , 66 , 70 , 71 , 75 , 77 , 78 , 87 , 91 , 93 ). This could be related to SES, as young people often have yet to reach a higher level of education, are still studying or in training, and consequently have a lower income ( 94 ).…”
Section: Discussionmentioning
confidence: 99%
“…To shed light on these gaps, we sought to construct an integrated network combining dimensions of empathy and symptoms of depression. There were three aims in the current research: (1) to investigate the relationship between different dimensions of empathy and symptoms of depression; (2) to identify positive and negative influential nodes that bridge empathy and depression by using bridge centrality indexes; and (3) to explore whether there are sex differences in the above network characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These transitions have exacerbated mental health concerns among the general population, particularly symptoms of depression. Symptoms of depression are characterized by anhedonia, sad mood, trouble with sleeping, fatigue, eating problems, guilt, trouble with concentrating, psychomotor agitation or retardation , and suicidal thoughts ( 1 ). These symptoms have been shown to affect long-term cognitive performance and quality of life ( 2 ).…”
Section: Introductionmentioning
confidence: 99%